Status and Mechanism of Insecticide Resistance in German Cockroach (Blattella germanica L.) Worldwide: A Literature Review - Resti Rahayu,; Intan Ahmad,; Muhammad Zai Halifiah Sinaga,; Risa Ukhti Muslima,; Robby Jannatan, (Tropical Life Sciences Research, 2025)
German cockroaches (Blattella germanica L.) are major residential pests, with reports of insecticide resistance emerging from numerous regions worldwide. This study aims to investigate the global distribution of insecticide resistance in German cockroaches, explore the underlying resistance mechanisms, identify the specific insecticides that have shown reduced efficacy, and examine how resistance has developed globally. A literature review was conducted, collecting relevant publications from journal databases such as Google Scholar, Science Direct, Wiley Online Library, and Oxford Academic Journal up to the year 2024. The keywords used in the search included "resistance," "insecticide," "Blattella germanica," and "German cockroach." The review included studies that provided data from field strains using contact-based assays. In total, 102 studies on resistance spanning 23 countries across four continents were identified. Resistance has been reported against 60 different insecticidal active ingredients, primarily from the pyrethroid and organophosphate classes, with varying degrees of resistance noted. Very high levels of resistance (RR > 100) were mostly recorded for pyrethroids. The predominant resistance mechanism observed involved metabolic mechanisms, particularly the increased activity of cytochrome P450 enzymes, followed by esterases and glutathione S-transferases (GST). Target-site mechanisms were also reported, including knockdown resistance (kdr) (L993F) and resistance to dieldrin (Rdl) (A302S). The combined mechanisms of resistance result in broad-spectrum resistance and potential cross-resistance. This review highlights the critical need for ongoing surveillance of insecticide resistance in German cockroaches and emphasises the urgency of developing more effective pest management strategies to address the escalating challenge of resistance.